Situation Report: Poland, 27 December 1962 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Christmas in Poland Church-State Relations Jaroszewicz on Comecon Polish-Belgian Property Settlement More on Air Crash Victims The Second Turoszow Power Set Agronomist Stations